Recovery of Terephthalic Acid by employing magnetic nanoparticles as a solid support - Elmira Ghamary (Polímeros, 2018)
Abstract The aim of this research work is focused on the improvement of Terephthalic acid recovery from PET wastes by using organically modified nano-Fe3O4@Cyanuric Chloride as the solid support. The performance of organically modified nano magnetic was examined in detail and the obtained results were compared with the unsupported reaction data. Required reaction time for complete glycolysis of the wastes, consumption of the solvent as well as catalyst decreases up 99%, 37.5% and 40% respectively. Result showed that nano-Fe 3O4@Cyanuric Chloride delivered good performance as solid support in depolymerizing of PET to the terephthalic acid.